1990
DOI: 10.1007/bf00228846
|View full text |Cite
|
Sign up to set email alerts
|

Conserved patterns of cortico-cortical connections define areal hierarchy in rat visual cortex

Abstract: The prevalence of reciprocal connections in the cerebral cortex indicates that they play a fundamental role in the processing of sensory information. We have investigated the laminar termination patterns of such paired connections between different visual cortical areas of the rat, and have found two basic projection types: one which includes layer 4 and a second which includes layer 1 and avoids layer 4. The projections from primary visual cortex (area 17) to extrastriate visual cortical targets in the cytoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 28 publications
7
64
1
Order By: Relevance
“…These findings differ from an earlier report by Miller and Vogt (1984); the difference may be attributed to the greater sensitivity and resolution of the tracer used by Coogan and Burkhalter (1990). The available evidence suggests that there are at least 3 hierarchical levels involving 5 visual areas in the rat.…”
Section: Other Speciescontrasting
confidence: 88%
See 1 more Smart Citation
“…These findings differ from an earlier report by Miller and Vogt (1984); the difference may be attributed to the greater sensitivity and resolution of the tracer used by Coogan and Burkhalter (1990). The available evidence suggests that there are at least 3 hierarchical levels involving 5 visual areas in the rat.…”
Section: Other Speciescontrasting
confidence: 88%
“…In the rat, a recent study by Coogan and Burkhalter (1990) has revealed consistent asymmetries in anterograde labeling patterns between visual areas, in a manner strongly analogous to the hierarchical relations we have described for primates. These findings differ from an earlier report by Miller and Vogt (1984); the difference may be attributed to the greater sensitivity and resolution of the tracer used by Coogan and Burkhalter (1990).…”
Section: Other Speciessupporting
confidence: 79%
“…Because perirhinal cortex lesions are sufficient to produce this visual object recognition memory deficit (Meunier et al 1993;Gaffan 1994;Buckley et al 1997) and entorhinal cortex lesions only produce transient effects (Leonard et al 1995), it appears that the perirhinal cortex is essential for visual object recognition memory. On the basis of anatomical evidence, a similar hierarchical organization has been uncovered in the rat between primary visual cortex and medial and lateral extrastriate visual cortex, temporal (TE 2 ) cortex, and perirhinal cortex (Deacon et al 1983;Miller and Vogt 1984;Coogan and Burkhalter 1990;Sanderson et al 1991;Vaudana et al 1991). The medial extrastriate visual cortex has been identified as an important substrate in mediating memory for visual object information .…”
mentioning
confidence: 87%
“…While bottom-up fibers terminate predominantly in cortical layer 4 of the target area, top-down fibers target mainly layer 1, [30][31][32][33][34] where they contact primarily apical dendrites of pyramidal neurons located in layers 2, 3, and 5. Traditionally, dendrites were thought to be passive conduction elements: the excitatory and inhibitory potentials induced at their synapses would be relayed to the cell soma simply via electrotonic spread, diminishing exponentially along the way.…”
Section: The Effects Of General Anesthetics On Apical Dendrites Of Pymentioning
confidence: 99%
“…It is by now well established that there are reciprocal anatomical connections at all stages of sensory processing for at least the visual, [30][31][32]65 auditory, 33,65 and somatosensory 34,65,66 modalities. In fact, area V1 receives top-down projections from more areas than it sends bottom-up projections to, and there appears to be a general predominance of topdown over bottom-up connectivity along the ventral visual pathway.…”
Section: Top-down Signals and Conscious Perception: What We Already Knowmentioning
confidence: 99%